Analisis Undang-Undang No 41 Tahun 2004 Tentang Wakaf Terhadap Yayasan Sosial Sabilillah An-Nahdliyah di Desa Gebang Kecamatan Sidoarjo Kabupaten Sidoarjo Sebagai Nadzir Badan Hukum - Moh. Alan Al Farizi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Sabilillah An-Nahdliyah Social Foundation is a foundation engaged in the Islamic social education and religious fields. The Sabilillah An-Nahdliyah Social Foundation, since its inception until now, still accepts waqf from the community, so it can be said that the foundation is a nadzir and is included in the nadzir research legal entity this aims to find out the requirements for the nadir of a legal entity in accordance with Law Number 41 of 2004 concerning waqf, especially in the Sabillilah An-Nahdliyah Social Foundation Gebang Village, Sidoarjo District, Sidoarjo Regency. The research method used is empirical legal research. The data used are primary data obtained through interviews and secondary data, namely Law Number 41 of 2004 concerning waqf. The results of the research show that the Sabilillah An-Nahdliyah Social Foundation has fulfilled the requirements as a nadzir of legal entity based on the provisions in the Waqf Law Number 41 of 2004, as stated in the deed of establishment number 10/10-11-2006. However, there are still provisions in the Law that have not been implemented, namely provisions related to the Ministry of Religion (Kemenag), namely reporting on the implementation of tasks, the right of the nadzir to receive guidance, and foundations need to coordinate with related parties. From the results of this study it can be concluded that the Sabilillah An-Nahdlivah Social Foundation as nadzir a legal entity based on the Waqf Law Number 41 of 2004 is